2005
DOI: 10.1007/s00414-005-0055-9
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death during anabolic steroid abuse: morphologic and toxicologic findings in two fatal cases of bodybuilders

Abstract: We report two cases of sudden cardiac death (SCD) involving previously healthy bodybuilders who were chronic androgenic-anabolic steroids users. In both instances, autopsies, histology of the organs, and toxicologic screening were performed. Our findings support an emerging consensus that the effects of vigorous weight training, combined with anabolic steroid use and increased androgen sensitivity, may predispose these young men to myocardial injury and even SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
99
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 21 publications
6
99
0
6
Order By: Relevance
“…Despite the elevated amount of AAS used, the Participant did not present any acute complications associated with AAS misuse; however, we have no data about past chronic effects, or what happened after the study. There is a large body of evidence suggesting that the indiscriminate use of AAS is not safe [9,37,38], and the literature provides many cases of serious cardiovascular events associated with anabolic steroid abuse by bodybuilders [39,40]. Additionally, many studies confirm that the abuse of anabolic substances produces profound and partly irreversible changes in various organs and systems, and that these changes tend to be related to the type, duration and dosage of anabolic steroids used [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the elevated amount of AAS used, the Participant did not present any acute complications associated with AAS misuse; however, we have no data about past chronic effects, or what happened after the study. There is a large body of evidence suggesting that the indiscriminate use of AAS is not safe [9,37,38], and the literature provides many cases of serious cardiovascular events associated with anabolic steroid abuse by bodybuilders [39,40]. Additionally, many studies confirm that the abuse of anabolic substances produces profound and partly irreversible changes in various organs and systems, and that these changes tend to be related to the type, duration and dosage of anabolic steroids used [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…According to the actual body of evidence, bodybuilders seem to risk their health in order to increase fat-free mass, and then again to lose fat; but end up, in fact, losing most of the fat-free mass previously gained [6,39,40]. Perhaps it would be more reasonable to gain smaller amounts of muscle mass while minimizing fat gain, and then adopting strategies for losing body fat while preserving lean mass, which would virtually eliminate the traditional preparatory and pre-competitive (also known as "bulking" and "cutting", respectively) phases and promote less aggressive variations in body composition together with less drug abuse.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Although testosterone has beneficial effects on the cardiovascular system, some studies linked the exogenous supraphysiologic doses of AAS with the development of cardiovascular abnormalities as hypertension, increased interventricular septum thickness, dilated cardiomyopathy, arrhythmia, heart failure and sudden cardiac death. (9,10) Muscle glycogen is an essential fuel for exercise training. Exercise produces a significant reduction in muscle glycogen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is believed that one of the factors responsible for the continuation of this problem is the wrong belief among athletes abusers that the adverse effects of these drugs are reversible effects and it can be easily treated later on after the sport competitions. This is absolutely not correct as there are many studies which confirmed the occurrence of irreversible adverse effects among the abusers such as cardiac disorders and chronic hepatitis [10,17,20] . Moreover, to realize how serious this health problem is, we have to know that governments in some countries spent millions to stand against this phenomenon, for example, in USA a great institute has been established to face this problem called (the association against steroids abuse) which provide free online medical information to the public regarding the health hazards of abusing these drugs [7,13] .…”
Section: Discussionmentioning
confidence: 99%